Chum salmon (Oncorhynchus keta) growth and temperature indices as indicators of the year–class strength of age‐1 walleye pollock (Gadus chalcogrammus) in the eastern Bering Sea. (May 2015) - Yasumiishi, Ellen M.; Criddle, Keith R.; Hillgruber, Nicola; Mueter, Franz J.; Helle, John H.
Abstract: Ecosystem‐based fisheries management requires the development of physical and biological time series that index ocean productivity for stock assessment and recruitment forecasts for commercially important species. As recruitment in marine fish is related to ocean condition, we developed proxies for ocean conditions based on sea surface temperature (SST) and biometric measurements of chum salmon ( Oncorhynchus keta ) captured in the walleye pollock ( Gadus chalcogrammus ) fishery in the eastern Bering Sea in three periods (July 16–30, September 1–15 and September 16–30). The main purpose of this paper was to evaluate Pacific salmon ( Oncorhynchus spp.) growth as a possible indicator of ocean conditions that, in turn, may affect age‐1 walleye pollock recruitment. Marine growth rates of Pacific salmon are the result of a complex interplay of physical, biological and population‐based factors that fish experience as they range through oceanic habitats. These growth rates can, therefore, be viewed as indicators of recent ocean productivity. Thus, our hypothesis was that estimated intra‐annual growth in body weight of immature and maturing age‐4 male and female chum salmon may be used as a biological indicator of variations in rearing conditions also experienced by age‐0 walleye pollock; consequently, they may be used to predict the recruitment to age‐1 in walleye pollock. Summer SSTs and chum salmon growth at the end of July and September explained the largest amount of variability in walleye pollock recruitment indicating that physical and biological indices of ocean productivity can index fish recruitment.